Analysing documents through fieldwork - Jacobsson, Katarina (Qualitative Research, 2025)
Ethnographic methods can advance our knowledge of a setting through its documents as well as help the researcher to grasp a document in its setting. This chapter contests the idea that the study of documents only refers to close analyses of text. Taking pictures of documents, asking about documents, and observing what people do with documents are approaches that can answer sociologically significant questions that cannot be addressed by merely analyzing the content of a text. Moreover, audio and video recordings of interactions over documents enable analyses of how documents are produced in situ as well as how documents shape and pattern interaction. The recognition of such aspects of documentary data requires fieldwork rather than deskwork.